Newborn screening for spinal muscular atrophy with EnLiteTM time resolved fluorescence resonance energy transfer polymerase chain reaction - Lehmusvaara, Mira (My University, 2019)
Spinal muscular atrophy (SMA) is a recessive neurodegenerative disorder, caused by mutations or a deletion in survival motor neuron (SMN) 1, the central gene for production of SMN protein. 95 % of all SMN cases are caused by a defect in the exon 7 of SMN1 (5q13). The SMN1 sequence is nearly identical with the SMN2 sequence, which is the secondary producer of SMN protein (produces only 10 % of the total SMN protein). SMN1 and SMN2 differ most significantly in exon 7, where a single nucleotide difference results in cytosine to thymine base change. In 95 % of all SMA cases, the C/T difference causes alternative splicing of the SMN2 transcript and therefore, lower production levels of SMN protein. PerkinElmer has developed a broad range of screening products for the detection of various newborn disorders. One assay platform is EnLiteTM which uses time-resolved fluorescence resonance energy transfer (TR-FRET) and polymerase chain reaction (PCR) to detect various analytes from dried blood spot samples. The aim of this study was to develop an assay for the detection of SMA using the EnLiteTM platform. The results of the study demonstrated that the EnLiteTM TR-FRET PCR assay, which utilizes SMN1 specific locked nucleic acid primers to amplify only the SMN1 gene, was successfully established; the assay can separate SMA positives from healthy and carrier samples.
Keywords: SMA, spinal muscular atrophy, newborn screening, SMN1, SMN2, LNA, FRET, PCR